Cellular resolution corneal imaging with extended imaging range - Wang, Lulu (2019)
Current optical coherence tomography (OCT) technology, which is used for imaging the eye’s anterior segment, has been established as a clinical gold standard for the diagnosis of corneal diseases. However, the cellular resolution level information that is critical for many clinical applications is still not available. The major technical challenges toward cellular resolution OCT imaging are the limited ranging depth and depth of focus (DOF). In this work, we present a novel ultrahigh resolution OCT system that achieves an isotropic spatial resolution of <2 µm in tissue. The proposed system could approximately double the ranging depth and extend the DOF using the dual-spectrometer design and the forward-model based digital refocusing method, respectively. We demonstrate that the novel system is capable of visualizing the full thickness of the pig cornea over the ranging depth of 3.5 mm and the border of the corneal endothelial cells 8 times Rayleigh range away from the focal plane. This technology has the potential to realize cellular resolution corneal imaging in vivo.